1999
DOI: 10.1034/j.1399-3003.1999.14a15.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TNF‐α, IFN‐γ and IL-β on normal human bronchial epithelial cells

Abstract: Effects of TNF-a, IFN-c and IL-b on normal human bronchial epithelial cells. C. Kampf, A.J. Relova, S. Sandler, G.M. Roomans. #ERS Journals 1999. ABSTRACT: Several diseases affecting the airways such as asthma are associated with both epithelial damage and increased levels of pro-inflammatory cytokines. To investigate the possible relation between cytokines and epithelial damage, the effects of tumour necrosis factor-a (TNF)-a, interferon gamma (IFN-c) and interleukin-1 beta (IL-1b) on normal human bronchial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…LOS has been shown to act as an epithelial cytotoxin in organ cultures of rat trachea (32). Further cytokine production by the epithelial cells could then lead to further epithelial cell damage (25,36). Finally, Joseph et al (33) suggested that LPS could act as a structural analog of ceramide and hence could stimulate host cells by mimicking the second messenger function of ceramide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LOS has been shown to act as an epithelial cytotoxin in organ cultures of rat trachea (32). Further cytokine production by the epithelial cells could then lead to further epithelial cell damage (25,36). Finally, Joseph et al (33) suggested that LPS could act as a structural analog of ceramide and hence could stimulate host cells by mimicking the second messenger function of ceramide.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, epithelial cells may act as sensors and play a key role in the modulation of the immune response to microbial infections (22,35,39). Further, IL-1 and TNF-␣ have been shown to damage respiratory epithelial cells (25,36), and H. influenzae has been shown to preferentially adhere to damaged epithelial cells (60,75). Thus, cytokineinduced respiratory epithelial cell damage may provide a means for H. influenzae to adhere to and invade host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the retrieved transplanted islets were prepared for and studied with transmission electron microscopy (TEM), as previously described (17). Briefly, the retrieved islets were fixed overnight in 2.5% (vol/vol) glutaraldehyde (Sigma-Aldrich) and 0.1 mol/l cacodylate buffer (Agar Scientific, Stansted, U.K.).…”
Section: Methodsmentioning
confidence: 99%
“…However, in BALF recovered from rats instilled with 250, 500, and 1,000 g of LPS, 27 Ϯ 4, 299 Ϯ 162, and 472 Ϯ 84 EU/ml were detected, respectively. Cytokines associated with LPS-induced inflammation and MCM (14,16,19) were measured by ELISA. IL-6 and TNF-␣ levels were essentially unchanged (100-500 pg/ml) at all doses compared with saline-instilled controls, but IL-1␤ levels increased significantly from 0.01 Ϯ 0.007 in saline controls to 0.45 Ϯ 0.1, 1.1 Ϯ 0.35, 2.6 Ϯ 0.9, 15.4 Ϯ 6.4, and 30.1 Ϯ 2.8 ng/ml at 50-, 100-, 250-, 500-, and 1,000-g LPS doses, respectively (P Ͻ 0.05 for all LPS doses).…”
Section: And Bcl-2 Expression At 2 3 and 4 Days Post-lps Instilmentioning
confidence: 99%